Is secondary prevention information before discharge adequate after percutaneous coronary intervention? - Henriksson, Catrin; Perk, Joep (Journal of Cardiology and Cardiovascular Medicine, 2019)
Introduction: Implementation of prevention strategies for patients with coronary artery disease (CAD) is essential, but many fall short of reaching their goals. Patients often perceive themselves as healthy and are less motivated to change lifestyle. To obtain better results patients need repeated information, preferably with motivational and person-centered approaches. Aims: To investigate whether health care providers inform CAD patients about risk factors and lifestyle changes at a percutaneous coronary intervention unit. Also to investigate whether the information given at discharge included secondary prevention management and if motivational and person-centered approaches were used. Methods: This is a descriptive, observational study that includes both a qualitative and quantitative design. Physicians and nurses working at a percutaneous coronary intervention (PCI) unit and physicians at a coronary care unit (CCU) participated. A staff nurse observed and noted what information the patients received at the PCI unit. At the CCU, observations regarding secondary prevention strategies during the discharge counselling were performed. Results: There were 50 observations made at the PCI unit. The information mainly consisted of tobacco consumption, physical activity and diet. During the 31 discharge counselling sessions the diagnosis, interventional procedure and medical treatment were frequently included. Most patients received little or no person-centered or motivational counselling. Conclusion: Nearly all patients at the PCI unit received information about the consequence of tobacco consumption, and more than half about the beneficial effects of physical activity. In contrast, the counselling at discharge need to focus more on behavioral changes and a motivational and person-centered approach.